Green synthesis of silver nanoparticles using Dodonaea viscosa extract and their antibacterial activity against Escherichia coli and Staphylococcus aureus - ZAINEB S. OMRAN; RANA A. MOHSIN; ENAS H. AL-ANI; TAQWA A. ABDEL DAYEM; ZEENA TARIQ SALIH (Asian Journal of Agriculture, 2026)
Abstract. Omran ZS, Mohsin RA, Al-Ani EH, Dayem TAA, Salih ZT. 2026. Green synthesis of silver nanoparticles using Dodonaea viscosa extract and their antibacterial activity against Escherichia coli and Staphylococcus aureus. Asian J Agric 10 (1): g100155. https://doi.org/10.13057/asianjagric/g100155. Silver nanoparticles (AgNPs) have attracted considerable attention as alternative antimicrobial agents, and plant-mediated synthesis represents an eco-friendly approach that minimizes the use of hazardous chemicals. In this study, Dodonaea viscosa AgNPs were examined to evaluate its activity against Escherichia coli and Staphylococcus aureus comparing to aqueous and ethanol extract. The phytochemical profile of the extract was analyzed by GC-MS, comparative analysis of both extracts indicated that aqueous extract contained a higher relative abundance of biologically relevant polar compounds. This observation supported its selection for subsequent green synthesis and antibacterial assays. The synthesized nanoparticles were characterized using FTIR, SEM, AFM, and EDX to confirm the functional groups involved in nanoparticle capping, as well as their morphology, particle size, and elemental composition. Antibacterial activity was evaluated against Gram-negative E. coli and Gram-positive S. aureus using the agar well diffusion method. The biosynthesized AgNPs, prepared from 0.5 and 1 mM AgNO₃, exhibited inhibition zones ranging from 16 to 29 mm, demonstrating enhanced antibacterial activity compared with the crude aqueous and ethanolic extracts. Overall, these findings indicate that D. viscosa-mediated AgNPs represent a promising eco-friendly antibacterial nanomaterial with improved efficacy. Future studies should include increased biological replication, robust statistical validation, and cytotoxicity assessment on mammalian cell lines to support potential biomedical translation.